Managing eating and drinking difficulties (dysphagia) with children who have learning disabilities: What is effective?. (July 2015) - Harding, Celia; Cockerill, Helen
People who work with children who have neurological and learning disabilities frequently need to manage the health and emotional risks associated with eating, drinking and swallowing (dysphagia). Some approaches can support children to develop oral feeding competence or to maximise their ability to maintain some oral intake supplemented with tube feeding. However, some clinicians feel that oral-motor exercises can support eating and drinking skills as well as speech and language development, whereas there is little evidence to support this. The implied "beneficial" association between oral-motor exercises, speech and swallowing skills gives a false impression in terms of future outcomes for parents and carers of children with learning disabilities. This paper considers oral-motor approaches in the remediation of dysphagia and the need for a cultural shift away from this view. Realistic and useful outcomes for people with learning disabilities need to be an essential part of therapeutic intervention.